Study of Wordwall Web Based Learning Media to Increase Student Learning Interest in Science Learning - Bernika Irnadialis Pramudita; Ali Sunarso (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to find out the study implementation of Wordwall web-based learning media to increase student learning interest in Natural and Social Science (IPAS) learning. This research is qualitative descriptive research, and did not aim to test a learning model by providing a certain stimulus, but to provide an in-depth description of changes in student interest in learning when obtaining web-based media in the students’ learning process. This research was conducted in SDN 08 Wanarejan which is located at St. Kerinci Taman, Rt 3/RW 3, Wanarejan, Taman, South Wanarejan, Wanarejan Sel. There are several kinds of games in Wordwall-based learning media that can be implemented. The implementation can be adjusted to the situation and conditions as well as the facilities and infrastructure of both schools and teachers and students personally as a form of flexibility in learning time.